Optically transparent membrane based on bacterial cellulose/ polycaprolactone - Barud, H. S. [UNESP]; Ribeiro, Sidney José Lima [UNESP]; Carone, C. L P; Ligabue, R.; Einloft, Sandra; Queiroz, P. V S; Borges, A. P B; Jahno, V. D. (FapUNIFESP (SciELO), 2013)
Optically transparent membranes from bacterial cellulose (BC)/polycaprolactone (PCL) have been prepared by impregnation of PCL acetone solution into dried BC membranes. UV-Vis measurements showed an increase on transparency in BC/PCL membrane when compared with pristine BC. The good transparency of the BC/PCL can be related to the presence of BC nanofibers associated with deposit of PCL nano-sized spherulites which are smaller than the wavelength of visible light and practically free of light scattering. XRD results show that cellulose type I structure is preserved inside the BC/PCL membrane, while the mechanical properties suggested indicated that PCL acts as a plasticizer for the BC membrane. The novel BC/PCL membrane could be used for preparation of fully biocompatible flexible display and biodegradable food packaging.
Keywords: Bacterial cellulose; Polycaprolactone; Transparent membrane; Acetone solution; Biodegradable food packaging; Optically transparent membranes; Visible light; XRD; Acetone; Cellulose; Mechanical properties; Plasticizers; Transparency; Membranes